2000
DOI: 10.1159/000030129
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Follow-Up of Breast Cancer Patients: Overview and Progress in the Use of Tumor Markers

Abstract: The role of serial measurement of serum tumor-associated antigens (TAA) in the postoperative follow-up of breast cancer patients is not considered by most authors. The authors of this article review the literature and original data showing benefits from the use of TAA in the postoperative follow-up of breast cancer patients. An increase in the lead time from the first pathological finding to the definite evidence of distant metastases has been observed in follow-up studies which have used TAA compared to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Number of subjects studied is small to establish a definite correlation between CA15-3 and bone scan findings. But many reported data from other authors support our results and suggests that elevated value of CA15-3 and bone scintigraphy are useful for early identification of bone metastasis in patients with breast cancer [1,2,9,11].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Number of subjects studied is small to establish a definite correlation between CA15-3 and bone scan findings. But many reported data from other authors support our results and suggests that elevated value of CA15-3 and bone scintigraphy are useful for early identification of bone metastasis in patients with breast cancer [1,2,9,11].…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have reported that the incidence of bone metastasis differs according to the clinical stage of breast cancer [2,[4][5][6][7][8]15]. Autopsy studies of breast cancer [9][10][11][12][13][14] have demonstrated a high proportion of breast cancer patients with bone metastasis (50-85%). The affinity of breast cancer to spread metastases in bones is one major reason for high mortality rate of breast cancer surgery is the treatment of choice for breast cancer patients without metastases.…”
Section: Introductionmentioning
confidence: 99%
“…CA15-3 level increased in 10% stage I breast cancer disease, 20% stage II disease, 40% stage III disease, and 75% with stage IV disease (Duffy 2006). Elevated levels of this biomarker were detected among certain benign diseases, primary breast carcinoma (Coveney, Geraghty et al, 1995) and in patients with advanced adenocarcinomas (Nicolini and Carpi 2000).…”
Section: El-bayoumy Asa Fawzy M Abdel-ghaffar Et Almentioning
confidence: 93%
“…The serum tumour marker level itself was much less important than the time-related change in values. In patients with a constant elevation or progressive increase of one or more tumour markers, tumour relapse was suspected, depending on whether the increase could be explained by any clear concomitant benign pathology indicated by the case history and/or laboratory exams [10][11][12].…”
Section: Tumour Markersmentioning
confidence: 99%
“…The lesions felt to be equivocal at liver echography were clarified by computed tomography or fine-needle aspiration cytology guided by liver echography when possible. The patients with equivocal radiological examinations and concomitantly not suspected of relapse with the CEA-TPA-CA15.3 tumour marker panel were regularly followed up as described above [8,9,12].…”
Section: Management Of Patients With Equivocal Bone Scintigraphy Chementioning
confidence: 99%